IMPLEMENTASI UNDANG-UNDANG NOMOR 20 TAHUN 2003 TENTAG SISTEM PENDIDIKAN NASIONAL TERHADAP ANAK YANG KURANG MAMPU DI KOTA SAMARINDA - Yovita Rindani (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Implementation of Law Number 20 Year 2003 on National Education System Against Underprivileged Children In Samarinda. Guided by mother Kunti Widayati, SH, M. Hum as Supervisor one and Dra. Sitti Aisha, SH, MM as Supervisor two. This study attempts to formulate the problem about Fulfillment Right to Education for underprivileged Children and Causes of Underprivileged Children Age Schools were not able to continue their education, and Government Participation In Handling Underprivileged Children In Samarinda City can not continue Education. The purpose of this paper, to explain how the application of the Rights of the Child's Rights Education that the presence of higher education can create quality human resource for the nation and that of the State as well as what things can be factors underprivileged children do not continue education, and the role of the government in dealing with the fulfillment of the right to education for underprivileged children. This research method is to use a normative juridical method is by using the resources of the library and Empirical Methods Juridical that the research in the field. Discussion of this paper describes a formulation of the problems associated with the cause of underprivileged children do not continue their education and the role of local government in the city of Samarinda handle fulfillment underprivileged children the importance of education. From the results of research and discussion, it is known that many factors cause underprivileged children do not continue their education primarily economic factors, and in this case the government is obliged to formulate a program for underprivileged children for the welfare of underprivileged children in the city of Samarinda.Keywords : National education system, education for disadvantaged children